The Effect of Tax Planning and Voluntary Disclosure on Company Value with Profit Quality and Audit Quality as Moderation - Kusuma Dewi; Syahril Djaddang; Edy Supriyadi (Kesatuan Press, 2021)
This study aims to determine the effect of tax planning and voluntary disclosure on firm value with earnings quality and audit quality as moderation in pharmaceutical industry manufacturing companies listed on the Indonesia Stock Exchange for the period 2009-2018. The sample in this study amounted to 80 samples determined by the purposive sampling method. Tests are carried out using the Moderated Regression Analysis (MRA) test using Eviews 9. The test results show that tax planning and earnings quality have a significant negative effect on firm value. Voluntary disclosure has a positive effect on company value. And the quality of earnings does not affect the value of the company. Tax planning and voluntary disclosure have a significant effect on company value when moderated by earnings quality. Tax planning and voluntary disclosure do not have a significant effect on company value when moderated by audit quality. Earnings quality and audit quality can strengthen the relationship between tax planning and voluntary disclosure of company value.